ALLELOPATHIC EFFECTS OF COMMON BRACKEN (Pteridium aquilinum (L.) Kuhn) ON GERMINATION AND GROWTH OF ECONOMICALLY IMPORTANT WEEDS - Mira, Yerly D.; Ramírez, Luis A.; Londoño, Luisa F.; Castañeda, Darío A. (Chilean Journal of Agricultural & Animal Sciences, 2021)
Pteridium aquilinum (L.) Kuhn is a cosmopolitan plant with great competitive abilities, including allelopathy. The search for plants with negative allelopathic effects on other undesirable plants has led to the discovery of new useful substances for weed control. The objective of this research was to evaluate the allelopathic effect of P. aquilinum on seed germination and growth of four economically important weeds: Bidens pilosa L., Brachiaria decumbens Stapf, Emilia sonchifolia (L.) DC. ex DC and Rumex crispus L. Two experiments were conducted under laboratory and greenhouse conditions using extracts and dried plant residues of P. aquilinum, respectively. For the first experiment, extracts of bracken were obtained using four different solvents (hexane, dichloromethane, ethyl acetate, and methanol) and applied to the test seeds; germination rates were determined. For the second experiment, dry residues of bracken were applied to the soil at concentrations of 2, 5, and 10% and their effect on weed growth variables was determined; a control treatment (no appliacation) was also included. In addition, the presence of some chemical groups associated with each type of extract was qualitatively detected. The extracts inhibited seed germination by 52 - 97% in all the studied species. Dichloromethane and methanol were the most efficient solvents, while E. sonchifolia was the most sensitive species. The dry residues of bracken reduced germination by 18 - 44% of all the weeds, as well as root length of Bidens pilosa (-30%) and Brachiaria decumbens (-82%). The phytochemical analysis showed the presence of flavonoids, tannins, and polyphenols in the extracts. These results suggest that P. aquilinum can be a good alternative for the biocontrol of the weeds under study and provide knowledge for the development of bioherbicides.